La capacità di aspirare. Immagini di futuro di figli e figlie di migranti a Reggio Calabria - Miceli, Simona (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
The article discusses the second-generation immigrant’s capacity to aspire in Postcolonial Italy, starting from a research which took place in Reggio Calabria. After defining some key concept such as “Postcolonial Italy” and “capacity to aspire”, I present the main hypothesis, which consist in considering the capacity to aspire as a way of resistance to Italian colonial unconsciousness. The qualitative methodology applied to the research involved carrying out some in-depth interviews. Therefore, in the last paragraphs the empirical data are presented by quoting some of the interview extracts. The main issues concern: second-generation immigrants’ approach toward their future as young people; their specific life experiences as people with foreign origins; the role played by the southern context in their future projects. This exploratory research suggests that capacity to aspire is a mode of agency, because who aspires to something is also someone who wants to change his/her current condition. This behaviour seems to be quite common among the people interviewed.